Comparison between supraglottic airway devices and endotracheal tubes in patients undergoing laparoscopic surgery: A systematic review and meta-analysis. Issue 33 (August 2016) - Park, Sun Kyung; Ko, Geum; Choi, Geun Joo; Ahn, Eun Jin; Kang, Hyun
Abstract : Supplemental Digital Content is available in the text Abstract: Background: Comparisons between the efficacies of supraglottic airway devices (SGAs) and endotracheal tubes (ETTs) in patients undergoing laparoscopic surgeries have yielded conflicting results. Therefore, in this meta-analysis, we compared the clinical performance and incidence of complications between SGAs and ETT intubation in laparoscopic surgery. Methods: A comprehensive search was conducted using MEDLINE, EMBASE, the Cochrane Central Register of Controlled Trials, and Google Scholar to identify randomized controlled trials that compared SGAs with ETTs in laparoscopic surgery. Results: In total, 1433 patients from 17 studies were included in the final analysis. SGAs and ETTs showed no difference in insertion success rate on the first attempt (relative risk [RR] 1.01, 95% confidence interval [CI] 0.99–1.03), insertion time (standardized mean difference 1.57, 95% CI −3.74 to 0.61), and oropharyngeal leak pressure (OLP) (mean difference −2.54, 95% CI −7.59 to 2.50). The incidence of desaturation (RR 3.65, 95% CI 1.39–9.62), gastric insufflations (RR 0.90, 95% CI 0.48–1.71), regurgitation (RR 0.98, 95% CI 0.02–49.13), and aspiration (RR 0.99, 95% CI 0.01–78.4) also showed no intergroup differences. However, the incidence of laryngospasm (RR 3.12, 95% CI 1.29–7.52), cough at removal (RR 6.68, 95% CI 4.70–9.48), dysphagia (RR 1.47, 95% CI 1.12–1.95) or dysphonia (RR 4.41, 95% CI 1.25–15.55), sore throat (RR 1.60, 95% CI 1.33–1.93), and hoarseness (RR 1.53, 95% CI 1.29–1.81) was higher in the ETT group than in the SGA group. Conclusions: The incidence of laryngospasm, cough at removal, dysphagia or dysphonia, sore throat, and hoarseness were higher in the ETT group than in the SGA group. However, the groups showed no differences in the rate of insertion success on the first attempt, insertion time, OLP, and other complications. Therefore, SGAs might be clinically more useful as effective airways in laparoscopic surgery.